Analisis Literasi Internet pada Aparatur Desa dengan Konsep Personal Capability Maturity Model (P-CMM) (Studi Kasus : Kecamatan Randudongkal) - Retno Waluyo; Gustin Setyaningsih; Muhammad Kholil (Politeknik Negeri Cilacap, 2019)
The development of information and communication technology (ICT) has brought change for the people of Indonesia. With ICT, people can more easily access various information and support work. But the problem that arises is the uneven penetration of ICT throughout Indonesia, including in the Randudongkal sub-district. This results in a digital divide and also weak ICT literacy. This study aims to describe the level of ICT Literacy, specifically internet literacy in the village apparatus in the Randudongkal sub-district. Measurement of internet apparatus of village apparatus in Randudongkal sub-district by using three indicators, namely basic knowledge, skills and utilization. The method for measuring literacy levels uses the Personal Capability Maturity Model (P-CMM). The results of internet literacy measurement research with three measurement indicators namely the internet have been used by village officials, but have not mastered and understood internet usage and currently, the level of internet apparatus in village apparatus is at level 2 by using Personal Capability Maturity Model (P-CMM).